Seasonal variation in composition, physicochemical properties and microbial load of raw milk: A comparative study between organized and unorganized dairy farms - Subarna Sarkar; Jitendra Saharia; Raj Jyoti Deka; Masuk Raquib; Purabi Kaushik; Das, Ajoy; Ranajoy Choudhury (Indian Journal of Dairy Science, 2025)
Raw milk is a highly perishable agricultural product that plays an important role in the dairy industry and human nutrition. Its composition and quality are influenced by various factors, including the type of dairy farm, seasonal changes, and storage conditions. The present study investigates the seasonal variation in the composition physicochemical properties and microbial load of cow raw milk in Guwahati, Assam. A total of 24 raw milk samples were collected from organized and unorganized cattle farms in different seasons for the study. In comparison to unorganized farms, organized farms had significantly higher (P < 0.01) levels of fat, SNF, protein, lactose, and ash. In comparison to summer milk, winter milk had higher (P < 0.05) levels of fat, SNF, protein, and ash except for the lactose content which was lower (P < 0.05) in winter. The pH of raw milk was also higher (P < 0.01) in the winter. Furthermore, organized farms had a higher (P < 0.01) raw milk specific gravity than unorganized farms. Both room and refrigeration storage temperatures caused significantly higher (P < 0.01) total viable count (TVC) and coliform count in milk during the summer. In conclusion, the findings of this study illustrated the dynamic nature of raw milk quality in various seasons and farm types. These variations have implications for raw milk quality and safety, emphasizing the need to implement appropriate management practices in dairy farms to maintain high-quality and safe milk throughout the year.